Effect of inquiry instruction on lower secondary students’ science process skills - Kotuľáková, Katarina; Dlholucký, Dávid; Palicová, Lucia; Šprláková, Lenka (Scientia in educatione, 2020)
Science curriculum emphasizes scientific knowledge, as well as science process skills (SPS) as the means that enable students to understand scientific concepts fully. Inquiry approach which develops these skills seems to be essential. The aim of the study was to investigate the effect of new designed material on SPS of students who had not experienced inquiry approach teaching before (experimental group) and compare it with SPS of students who use common material (textbooks) and dominant deductive teacher-centered approach still typical for Slovak schools (control group). Study was carried out with 80 eight grade pupils. Pupils’ inquiry reports were analyzed. After intervention the experimental and the control group solved test tasks and results were compared. Results showed that inquiry approach had a significant effect on improvement of pupils’ SPS, especially the ones with low success rate at the beginning, proposing how to test formulated hypothesis and inferring. Some common features of the most problematic SPS were identified. Our findings contribute to the discussion about importance of investment into developing procedural knowledge.